USE OF STERILISED NYLON MOSQUITO NET MESH IN INCISIONAL HERNIAS. - DR. VISHAL DUBEY (International Journal of Pharma and Bio Sciences, 2014)
Hernioplasty is mainstay in treatment of abdominal wall hernias including incisional hernias. But in the developing countries like India everyone can not afford the commercial mesh used for this procedure. So, in this study we used sterilised nylon mosquito net mesh in our patients, efficacy of which has been proved already in the repair of both inguinal and incisional hernias. In this study consecutive patients of incisional hernias, admitted in R.D. Gardi Medical College, Ujjain from March 2008 to March 2014 were included. The included patients were informed and consent was taken for the use of mosquito net mesh. The patients who gave consent for the use of sterilised mesh made the case group in whom mosquito net mesh was used. Those who refused for mosquito net mesh were included in the control group in whom hernia repair was done by conventional non-mesh methods. During the follow up in the post operative period up to six months the main complications in the case group were prolonged discharge (12%), seroma (9.33%), stitch abscesses (8%) and gross infection (5.3%). There was no recurrence noted in the case group. In the control group the gross infection was found in 8 (11.76%) cases followed by prolong infection in 6 (8.82%) cases, seroma and stitch abscess in 5 (7.35%) cases. The recurrence was found in 2(2.94%) cases. Cost of locally purchased and sterilised nylon mosquito net mesh of standard size 10 x15 cm used here was 2 rupees [about 0.0404US ] as compared to 800 rupees [16.16 US] for the prolene mesh of same size. On the basis of this study, we can say that properly sterilised mosquito net can be a mesh of the choice in the institutional setups for incisional hernia surgery in the rural areas of the developing countries like India where the population cannot afford the higher cost of surgery with commercially available costly meshes. Also it was found safer to use and can be used in place of conventional methods of primary repairs.